1995
DOI: 10.1063/1.359569
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and structure of sputter-induced cones on nickel-seeded silicon

Abstract: Microprotrusions, or cones, grown on monocrystalline Si obliquely sputtered with Ar+ ions, while being supplied with Ni ‘‘seeds’’ by sputtering, were observed by scanning and transmission electron microscopy. At temperatures lower than 400 °C, Ni atoms were deposited on the upper cone slope receiving the high fluxes of seeds, resulting in the development of ‘‘delta-winged’’ cones. Seed layers were Ni for substrate temperatures below 200 °C and nickel silicide for temperatures above 200 °C, and they were silici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The seed layers thus formed serve to protect the cone from ion erosion, thereby sustaining the steady-state evolution of the cone. 9 Whereas cones developed from intrinsic sources ͑such as defects͒ are nonequilib-rium formations. This kind of cone or pyramid tends to be unstable in most cases; the structures will be eroded by prolonged sputtering.…”
Section: Discussionmentioning
confidence: 99%
“…The seed layers thus formed serve to protect the cone from ion erosion, thereby sustaining the steady-state evolution of the cone. 9 Whereas cones developed from intrinsic sources ͑such as defects͒ are nonequilib-rium formations. This kind of cone or pyramid tends to be unstable in most cases; the structures will be eroded by prolonged sputtering.…”
Section: Discussionmentioning
confidence: 99%
“…The additional weak diffraction spots originate in the Si‐based superstructure in the central tip zone. They present one‐dimensional and two‐dimensional orderings along three zone directions of 1–10, [100] and [1‐1‐1] 17. In the real space, the superstructure can result from a commensurate modulation induced by Mo atoms periodically replacing Si atoms in the particular direction.…”
Section: Resultsmentioning
confidence: 99%
“…Morishita et al illustrated a layer of epitaxial Mo seed film deposited on the tip of Cu cones 18. Fujimoto et al reported that the tips of Si cones were composed of a heteroepitaxial structure of NiSi 2 ‐Si‐NiSi 2 at a target temperature of 400 °C 7. Besides Ar ions, incident particles in the present system should also include ions from the seed materials and the recoiled ions from the Si substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative to the approach of Dev et al is fabricating prealigned metal zinc nanostructures on zinc foils as a template for subsequent thermal oxidation producing prealigned ZnO nanostructures. It has been shown that cone-shaped nanostructures can be prepared using ion beam sputtering on Cu, 3 Ag, 4 Al, Fe, 5 Si, 6 Ge, 7 InP, 8 GaN, GaP, Al 2 O 3 , 9 and graphite. 10 Two formation mechanisms have been proposed, a whisker growth 11 and a left-standing process.…”
Section: Introductionmentioning
confidence: 99%